2014
DOI: 10.1007/s10792-014-9988-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the ganglion cell complex and structural measures of the optic disc and retinal nerve fiber layer in glaucoma

Abstract: To correlate the ganglion cell complex (GCC) parameters with structural measures of the optic nerve head (ONH) and retinal nerve fiber layer (RNFL) as evaluated by Fourier-Domain optic coherence tomography (OCT). This retrospective study included patients with glaucoma, ocular hypertensive patients and glaucoma suspects who had previously undergone OCT examination with the RTVue-100. The parameters of GCC (average, superior, inferior, focal loss volume [FLV], global loss volume [GLV]) were correlated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…GCC analysis has a significant correlation with RNFL study in both glaucoma patients and healthy individuals and probably has a higher diagnostic ability than RNFL, to detect the early glaucomatous damage [13]. Instead The correlations of GCC indices with the optic disk parameters are not equally strong (r>0,2), especially for GLV and FLV [14]. In patients with primary open angle glaucoma and glaucoma suspects patients the progression of the GCC damage follows the perimetric defects (P = 0.007) and presents a strong correlation (r > 0.60) with the visual fields indices [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…GCC analysis has a significant correlation with RNFL study in both glaucoma patients and healthy individuals and probably has a higher diagnostic ability than RNFL, to detect the early glaucomatous damage [13]. Instead The correlations of GCC indices with the optic disk parameters are not equally strong (r>0,2), especially for GLV and FLV [14]. In patients with primary open angle glaucoma and glaucoma suspects patients the progression of the GCC damage follows the perimetric defects (P = 0.007) and presents a strong correlation (r > 0.60) with the visual fields indices [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nogueira et al [16] study results displayed that there was a significant association between GCC thickness and optic disc (p=0.016). Also, Bresciani-Battilana et al [24] reported that rim area showed the best correlation with average GCC (r=0.583).…”
Section: Fig 5 Correlation Between Average Rnfl Thickness and Papille...mentioning
confidence: 94%